The effect of heating temperature on 3D print filament diameter consistency produced by HDPE and LDPE plastic extrusion machine - Rijekki, Nanda Fajar; Sari, Nurlia Pramita; Faizin, Akhmad; Rosady, Siti Duratun Nasiqiati (Journal of Engineering and Applied Technology, 2024)
3D printing technology is rapidly growing in the industrial world, especially with the Fused Deposition Modeling (FDM) method that uses thermoplastic filament filaments. The manufacture of these filaments requires extrusion machines and plastic seeds, with filament diameter as the main indicator of 3D Print quality. This study aims to analyze the effect of variations in heating temperature on the consistency of the diameter of the results of extrusion machines for High Density Polyethylene (HDPE) plastics at temperatures of 160°C, 180°C, 200°C, 220°C, and 240°C and Low Density Polyethylene (LDPE) at temperatures of 160°C, 170°C, 180°C, 190°C, and 200°C. Each temperature variation has six filament samples, with the diameter measured every 1 cm for five measurements using a screw micrometer, resulting in 30 data per temperature variation. The data is processed using Statistical Process Control (SPC) and Capability Process methods. Based on data analysis with control chat, it can be concluded that each temperature variation produces diameters that are within the control limits, allowing capability process testing. Process Capability has been conditioned, resulting in large process variations compared to the established specification range, indicating imbalances and inconsistencies in filament production so that filament diameters are often out of specification limits. The conclusion of this analysis is that temperature variation has a significant effect on the consistency of filament diameter resulting from extrusion machines with HDPE and LDPE plastic seed materials. In addition, based on variations in temperature data that produce the best filaments, the temperature is 220°C for HDPE plastic and 190°C for LDPE plastic.